BURSA NILAI: MODEL PENUMBUHAN NILAI-NILAI KARAKTER BANGSA - Maman Rachman; Margi Wahono (Universitas Negeri Malang, 2018)
This article has analyzed the value exchange-based learning model as an efforts to de- velop character values in students. The approach used a qualitative-quantitative mixed method. The qualitative approach used to synthesize the steps of the learning model. Whereas the quantitative approach used to test the model qualifications based on student responses and motivation. Re- search subjects were lecturers and students. Data collection done through interviews, observation, documentation, intake of experts and practitioners, focus group discussions, and questionnaires. Data analysis carried out interactively and descriptive statistics. The results of the analysis showed that the value exchange-based learning model carried out through elaboration steps in crisis situa- tions of character values; classroom management and teaching materials (classical), exploration of character crisis situations; crisis solution of character (group) values; growth of character values; analysis, reflection repetition, and (classical) feedback. Forms of character that develop are demo- cratic, nationalism; concern. compliance with rules; honesty; logical thinking, critical, creative, and innovative. Responding to model qualifications was very strong followed by very high student motivation. DOI: http://dx.doi.org/10.17977/um019v3i12018p089